Pollutants removal, greenhouse gases emission and functional genes in wastewater ecological soil infiltration systems: influences of influent surface organic loading and aeration mode - Jingna Chen (IWA Publishing, 2021)
The influences of influent surface organic loading rate (SOLR) and aeration mode on matrix oxygen, organic matter, nitrogen, phosphorus removal, greenhouse gases emission and functional gene abundances in lab-scale wastewater ecological soil infiltration systems (WESISs) were investigated. In WESISs, intermittent or continuous aeration improved oxygen supply at 50 cm depth and hardly changed anaerobic condition below 80 cm depth, which enhanced chemical oxygen demand (COD), NH4+-N, total nitrogen (TN) removal, the abundances of bacterial 16S rRNA, amoA, nxrA, narG, napA, nirK, nirS, qnorB, nosZ genes and reduced CH4, N2O conversion efficiencies with SOLR of 16.9 and 27.6 g BOD/(m2 d) compared with non-aeration. Increased SOLR resulted in high TN removal, low N2O emission in aeration WESIS, which was different from non-aeration WESIS. High average COD removal efficiency of 90.7%, NH4+-N removal efficiency of 87.0%, TN removal efficiency of 84.6%, total phosphorus (TP) removal efficiency of 93.1% and low average N2O emission rate of 12.8 mg/(m2 d) were achieved with SOLR of 16.9 g BOD/(m2 d) in intermittent aeration WESIS. However, continuous aeration WESIS obtained high average removal efficiencies of 90.1% for COD, 87.5% for NH4+-N, 84.1% for TN, 92.9% for TP and low average emission rate of 13.1 mg/(m2 d) for N2O with SOLR of 27.6 g BOD/(m2 d). Aeration could be an optional strategy for WESISs to achieve high pollutants removal and low CH4, N2O emission when treating wastewater with high SOLR. HIGHLIGHTS SOLR and aeration mode significantly affected pollutants removal and GHGs emission.; Aeration obtained high pollutants removal and low CH4, N2O conversion efficiencies.; Aeration enhanced the abundances of bacterial 16S rRNA and nitrogen removal genes.; SOLR of 16.9–27.6 g BOD/(m2 d) was suggested for aeration WESISs.;